Crise Ivoirienne Et Mutations Dans La Gestion Des Ressources Humaines De La Sucrerie Africaine De Cote d’Ivoire (SUCAF-CI) - Silué Iguélédjôh Annick (European Scientific Journal, ESJ, 2016)
This article describes how the 2002 military and political crisis in Côte d’Ivoire has led the path to a new negotiation process of improving the working relationships between staff members of SUCAF-CI (African Sugar Company in Côte d’Ivoire). Along with that crisis some problems arose and made the company senior staff to think of ways of solving them and also of taking control of the working environment. In so doing they resorted to new rules in Human Resources Management policy. Definitely, this study describes how significant the conflicts induced by the organizational change have been for all the company workers. It resulted in bringing the employees to adopt a new working habit in order to resist and keep up with that change. Essentially, negotiation will be the key word to resolve conflicts within SUCAF-CI and namely to bring all the workers around the table to draft a new social pact as part of a consensual HRM policy.